FATWA SHEIKH AḤMAD KHAṬĪB AL-MINANGKABĀWĪ (DS 0003 00018): A Jāwī Ulama’s Response to the Heterodoxy of Sufism - Jajang A Rohmana (AL-TAHRIR, 2023)
This article discusses the fatwa of a Jāwī or Malay-Indonesian archipelago ulama who taught in Mecca in the early twentieth century, Sheikh Ahmad Khatib Minangkabau (1860-1916). He was issuing fatwa on heterodox sufism in the archipelago. His fatwa is written in a manuscript from Ogan Komering Ilir entitled Fatwa Sheikh Aḥmad Khaṭīb al-Minangkabāwī (DS 0003 00018). The manuscript has been digitized by DREAMSEA in 2019. This manuscript was probably written when he became a lecturer in Mecca between 1887-1914. It contains questions and answers about the existence of the name Muhammad and rūḥ al-quds (holy spirit) in the human heart that commands the body. Using a social history approach, this study shows that the Fatwa manuscript shows the response of Jāwī ulama who were increasingly influenced by the teachings of Islamic reformism. Ahmad Khatib stated that it was impossible for the spirit of Muhammad and rūḥ al-quds to exist in the body. For him, Muhammad is a human being and the holy spirit is Gabriel, an angel. He stated that whoever believes that both Muhammad and Gabriel are in his/her body is wrong and misguided, and if he/she believes that they are eternal, then he/she is a disbeliever. Ahmad Khatib’s fatwa indicate an attempt to purge the heterodoxy of sufism continually by Sunnī ulama in the early twentieth century.